Hierarchical formation of Ni sulfide single walled carbon nanotubes heterostructure on tin-sulfide scaffolds via mediated SILAR process: Application towards long cycle-life solid-state supercapacitors. Issue 12 (15th June 2022) - Kumar, NIraj; Mishra, Dhananjay; Gi Seo, Seung; Na, Taehui; Jin, Sung Hun
Abstract: For the enhancement of cyclic life in supercapacitors (SCs), hierarchically formed metallic single-walled carbon nanotubes (m-SWNTs) mediated nickel sulfides (c–NS–TS) heterostructures are synthesized on tin-sulfides (TS) scaffolds via successive ionic layer adsorption and reaction (SILAR) process. As compared with bare SnS2, c–NS–TS formation has effects to improve electrical conductivity and to reduce volume expansion in bare SnS2 scaffolds, leading to better specific capacitance and rate performance in SCs. The film structure, morphology evolution, and capacitive kinetics of c–NS–TS thin films are systematically investigated to understand the behind mechanism on the significantly improved electrochemical performance. Thus, the incorporation of highly conductive, nano-scale m-SWNTs (c–NS–TS) yields high capacitance (1120 Fg -1 ) with excellent cyclic stability (95%), possibly due to inter-linkage of pure m-SWNTs in the heterostructure. For the enhanced electro-kinetic activity, this is strongly affected by the preferable formation on 3-dimensional c–NS–TS heterostructures, along with highly conductive m-SWNTs, leading to the initiation of the electroactive sites for enhanced electro-kinetic activity. For practical validation on applicability, LED lighting is successfully demonstrated, anticipating that the synthesis concept and its electrochemical properties will contribute to next-generation high-performance SC devices.